Regional effects of producer services on manufacturing productivity in China. (August 2018) - Yang, Fiona Fan; Yeh, Anthony G.O.; Wang, Jiejing
Abstract: As specialized supportive activities, producer services have been well documented to contribute significantly to the growth of manufacturing productivity. Despite the acknowledged tradability of producer services, the regional effects of these services have received relatively limited attention, thereby preventing a substantial understanding of the relationship between producer services and manufacturing performance. Consequently, this study analyzes the regional effects of producer services on manufacturing productivity in China based on firm-level data. Apart from analyzing the extent to which external producer services positively contribute to the growth of manufacturing productivity, the range or hinterland that such services can possess to benefit manufacturing firm operations is also identified. Our findings suggest that manufacturing productivity in China is positively associated with producer service inputs, and the effects of producer services on manufacturing productivity are not limited to local firms but are regional oriented. This outcome is crucial to understand the spatial relationship between manufacturing and producer services and the development of regional economies in developing countries where manufacturing and producer services have simultaneously expanded. Highlights: This study investigates the regional effects of producer services on manufacturing productivity in China based on firm-level data. Findings suggest that manufacturing productivity in China is positively associated with producer service inputs. The effects of producer services on manufacturing productivity are not limited to local firms but are regional oriented. Producer services can overcome the distance barrier to benefit the operation of non-local manufacturers.